1999
DOI: 10.3354/dao035213
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazolium-based cytotoxicity assay to determine anti-protozoal activity against the scuticociliate Anophryoides haemophila

Abstract: Anophryoides haemophila is a ciliated protozoan that causes 'bumper car' disease in American lobster Homarus americanus. Currently, there are no effective pharmaceuticals approved for use to treat the disease, which can be a significant source of mortality in lobster holding facilities. We have modified a tetrazoliurn-based cytotoxicity assay to determine the anti-protozoa1 activity of compounds towards A , haemophila. To obtain reproducible results, A. haemophila maintained in continuous culture were preferab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(9 reference statements)
1
4
0
2
Order By: Relevance
“…Furthermore, no pathology was observed, when the drug was administered to uninfected lobsters. The drug has been also shown effective during in vitro trials (Novotny et al, 1996, Cribb et al, 1999. As there is no effective treatment for the control of bumper car disease, on the basis of the results of the present study, we suggest that pyrimethamine is a good drug for the treatment of A. haemoplila infection in lobsters.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Furthermore, no pathology was observed, when the drug was administered to uninfected lobsters. The drug has been also shown effective during in vitro trials (Novotny et al, 1996, Cribb et al, 1999. As there is no effective treatment for the control of bumper car disease, on the basis of the results of the present study, we suggest that pyrimethamine is a good drug for the treatment of A. haemoplila infection in lobsters.…”
Section: Discussionsupporting
confidence: 55%
“…Επίσης, δεν παρα τηρήθηκαν παθολογικές αλλοιώσεις, όταν το φάρμακο δό θηκε σε μη μολυσμένα άτομα. Εξάλλου, το φάρμακο έχει αποδειχθεί ότι είναι αποτελεσματικό και σε in vitro δοκι μές (Novotny et al, 1996, Cribb et al, 1999.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Oxytetracycline and amprolium had little to no effect on the ciliate motility. Cribb et al (1999) developed an in vitro tetrazolium-blue formazan assay for testing the efficacy of various antibiotics against A. haemophila. They found that 100 M lasalocid or pyrimethamine was cytotoxic to the ciliate over 24 hours.…”
Section: Pathogens Parasites and Other Symbionts 161mentioning
confidence: 99%